Barriers and impediments to transformational government: insights from literature and practice. (22nd April 2011) - Van Veenstra, Anne Fleur; Klievink, Bram; Janssen, Marijn
Transformational government (t-government) has been introduced as a new stage of e-government aimed at realising structural changes and greater benefits in the public sector. Yet, there are many impediments blocking transformation, and there is limited insight in these barriers. In this paper, impediments for t-government are investigated by conducting a literature review and carrying out three case studies. The impediments found in literature were confirmed and extended using the case studies. Impediments simultaneously occur on the governance, organisational and managerial, and technical level and need to be addressed in concert. Research on transformation can benefit from understanding these interrelated impediments.